Pengaruh pembelajaran senam irama terhadap peningkatan kemampuan gerak dasar manipulatif dalam mningkatkan teknik dasar permainan kasti - Pajar Anugrah Prasetio; Agus Gunawan; Endun Muhamad Laduni (COLLASE (Creative of Learning Students Elementary Education), 2023)
The aim of this research is to find out and describe the differences in the ability to throw, catch and hit the ball in the basic techniques of playing rounders as manipulative movement abilities before and after learning rhythmic gymnastics. This research includes quantitative research with a pre-experimental approach, with a one group pre-test post-test design. The subjects of this research were 29 class IV students at SD Negri 1 Ranbatan, Ciniru, Kuningan. In carrying out the research, it started by giving a test in the form of test items in the pretest, then providing treatment by applying rhythmic gymnastics learning in 5 meetings, then ending by giving the test items again at the posttest. Based on the results of data analysis, the average throwing test score increased from 19 to 32, then the average catching score increased from 10 to 14 and the average hitting score increased from 21 to 27 so it can be concluded: (1) there are differences in throwing and catching abilities. and hitting the ball in the game of rounders before learning rhythmic gymnastics with the ability to throw, catch and hit the ball in the game of rounders after learning rhythmic gymnastics. (2) there is an increase in basic manipulative movement abilities in the game of rounders by using rhythmic gymnastics learning.